Detection of Brucella antibodies in sera of dogs using Rose Bengal test: Saleem Amin Hasso1 and Eman Saleh Serian2 - Hasso, Saleem Amin (The Iraqi Journal of Veterinary Medicine, 2012)
Using the rose Bengal test 114 blood samples collected from dogs , and tested for Brucella antibodies , (30.7 % ) were found positive for Brucella antibodies while (64.3 % ) were found negative for Brucella antibodies .Key words : Brucella antibodies , dogs .